TOURISM SATELLITE ACCOUNT A STATISTICAL TOOL TO ANALYSE TOURISM ROLES - Wiyashya, Ida Bagus Made (Pusat penelitian & Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2004)
This article tries to explore the Tourism Satellite Account (TSA) results in severalcountries. It is a statistical tool used to derive tourism multiplier in a country'seconomy. In preparing a TSA an input-output model is applied. Resultsshow differences in tourism roles in a country's economy due to the sizeand leakage in tourism